Belimbing tunjuk, a chemistry and cool in jar: nutritious and satisfying local fruit / Nursuria Mahrif ... [et al.] - Mahrif, Nursuria; Johan, Roza Jasmin; Rajali, Radiana; Majang, Trena; Nur Sofia, Khofi (Universiti Teknologi MARA, Kedah, 2019)
This project is to prepare a home-made jam using an easy-to-find fruit which is “Belimbing Telunjuk” which is in contrast to starfruit; common in the Carribean. To add creativity and innovative way of preparing, we add lemon, honey, and sugar as additional ingredients. The objectives are to offer varieties of jam flavour in the market and produce alternative nutritious product. The novelty of this product is using the “belimbing telunjuk” as compared to other fruit jams sold on shelves in the market. The fruit itself is considered ‘evergreen’ and has long been used in most Malay cooking in the local villages. Besides the fruit contains high nutrients which may provide natural cure and supplement for our body as it is low in calories. ‘Belimbing tunjuk’ also contains key minerals and electrolytes for healthy cell regeneration and stabilizing heart rate and blood pressure and counteracting negative effects of too much sodium. For those villagers who know the usage of this fruit, it is commonly used to help combat hangovers. With its sour to sweet taste of the fruit; enables the users to experience the unique value of the fruit as well. This product can enter the market very well because of the potential needs from all the users. This prepared jam will be able to offer variety on the long-sold jams in the market. Hence, intermittently, with this product, it will provide endless advantages for some people who love local fruits.